On the role of inelastic scattering in phase-plate transmission electron microscopy - Hettler, Simon Josef; Wagner, Jochen; Dries, Manuel; Oster, Marco; Wacker, Christian; Schröder, Rasmus R.; Gerthsen, Dagmar (Ultramicroscopy, 2015)
The phase contrast of Au nanoparticles on amorphous-carbon films with different thicknesses is analyzed using an electrostatic Zach phase plate in a Zeiss 912Ω transmission electron microscope with in-column energy filter. Specifically, unfiltered and plasmon-filtered phase-plate transmission electron microscopy (PP TEM) images are compared to gain insight in the role of coherence after inelastic scattering processes. A considerable phase-contrast contribution resulting from a combined elastic-inelastic scattering process is found in plasmon-filtered PP TEM images. The contrast reduction compared to unfiltered images mainly originates from zero-order beam broadening caused by the inelastic scattering process. The effect of the sequence of the elastic and inelastic scattering processes is studied by varying the position of the nanoparticles, which can be either located on top or at the bottom of the amorphous-carbon film with respect to the incident electron beam direction.